Dampak Pungutan Liar Oleh Organisasi Masyarakat Bagi UMKM (Usaha Mikro, Kecil, dan Menengah) - Galih Angga Mahendra; Laili Norma Faseh; M. Alauddin Robbani; Mashudi Mashudi (Jurnal Multidisiplin Ibrahimy, 2025)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of inclusive eco-nomic development in Indonesia. However, in addition to internal challenges, MSMEs also face external threats in the form of extortion practices carried out by unscrupulous community organizations (CSOs). This study aims to examine conceptually and liter-arily the practice of extortion by mass organizations, its impact on MSMEs, and how it creates economic burden and legal uncertainty for small business actors. The method used is a literature review by tracing academic journals, books, and relevant recent news. The results of the study show that extortion practices increase the operational costs of MSMEs, reduce competitiveness, and widen economic disparities. In addition, this practice also undermines the ideal role of mass organizations as development partners and reduces the level of public trust in the legal system. These findings em-phasize the importance of academic and policy attention to non-structural external threats that have so far received less attention in the discourse of populist economics.